Climatology of 24-hour north Atlantic tropical cyclone movements - Cry, George W; National Hurricane Research Project; United States. Weather Bureau (Washington, D.C. : U.S. Dept. of Commerce, Weather Bureau, 1961)
Bibliography: p. 17-18 Mode of access: Internet.